Internal Control System as a Moderating Variable in The Analysis of Transparency in Management of Village Fund Direct Cash Assistance on Village Government Performance - Mirasty Manggalatu; Munzir Munzir; Musriani Musriani; Mervin Irian Sadipun Komber; Putrawansyah; Andi Rosdinaman Budi; Yusron Difinubun; April Sisilia Erawati Tharob; Ferdinandus Syama (IECON: International Economics and Business Conference, 2025)
Village fund management is an important challenge for village officials that can create crucial potential in the use of these funds. Therefore, this study aims to examine the effect of transparency in the management of village fund direct cash assistance (BLT-DD) on the performance of the Sekban Village Government, Fakfak Regency, with the internal control system as a moderating variable. The study used a quantitative approach with a population of 50 BLT-DD recipients in Sekban Village in 2024, and the sample was taken by purposive sampling. Data were collected through a questionnaire with a Likert scale and analyzed using multiple linear regression techniques and moderation tests. The results of the study indicate that: (1) transparency has a positive and significant effect on village government performance, (2) the internal control system moderates the effect of transparency on village government performance. This study provides theoretical contributions to the development of accounting science and village government management, as well as practical implications for increasing the effectiveness of BLT-DD management through the application of transparency, and an optimal internal control system.